More answers

(3x - 2)(x + 1) are the factors if the equation equals 0, making x = two-thirds or -1.

Q: What is 3x squared plus x - 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

(x + 2)(x + 1)

(x + 2)(x + 1)

It is a quadratic expression and can be factored into: (3x+1)(x+2)

Let square = [x] -4+3*(-2)*[-4]+[3x-2x]=-4-6-2+[x]=-12+[x]The answer is negative 12 plus squared x.

3x2 + 5x + 2 is a quadratic expression that can be factored as follows: 3x2 + 5x + 2 = 3x2 + 3x + 2x + 2 = 3x(x + 1) + 2(x + 1) = (3x + 2)(x + 1)

Related questions

x^2 + 3x + 2/(-3x) - x^2 - 2=3x-2+2/(-3x)=3x-2-2/(3x)

x^2+2x^2=3x^2

(3x + 3y)(x + y) = 3(x + y)2

x3+3x2+3x+2 divided by x+2 equals x2+x+1

(x + 2)(x + 1)

(x + 2)(x + 1)

-1

3x2+x-2 = (3x-2)(x+1) when factored

(x^2 - 3x + 5)(x^2 + 3x + 5)

(3x-2)(x-2)

(x - 4)(3x - 2)

(3x - 2)(x + 8)